Advanced Biliary Interventions: Gastrointestinal or Interventional Radiology Approach - Naranjo, Miguel; Ferral, Hector; Chavez, Roberto (Digestive Disease Interventions, 2023)
The management of biliary pathology can be surgical, endoscopic, or percutaneous. Percutaneous interventions play an important role in the management of patients. Biliary drainage is the initial step in most radiological interventions, including percutaneous transhepatic cholangioscopy. It can be palliative or curative. We present here the different techniques available from interventional radiology. The purpose of this review article is to investigate the latest published evidence on percutaneous minimally invasive approach of biliary disease and outline current trends.
Keywords: transhepatic biliary drainage; percutaneous transhepatic cholangioscopy; biliary stents; endobiliary biopsy; biliary stone